(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
Public universities in Kenya are operating in an environment which is faced with a lot of competition. This is because over the years the number of Universities has drastically increased and there has been advancement in technology bringing about shortage of talent. Institutions are increasingly looking at talent as a unique asset that can provide sustainable competitive advantage and superior performance. This research sought to establish the influence of talent attraction on organizational performance. The study was guided by Maslows theory. The target population for the study was; managers, academic staff and non-academic staff in campuses of public universities in county government of Nakuru, Kenya. Stratified random sampling and simple random sampling techniques were used to determine the sample of each stratum of various sub population of total sample unit size of 102. Structured questionnaire was used to collect data. The instrument was pilot tested to ascertain the reliability of the research instrument using Cronbach Alpha. The reliability of the research instrument was found to be 0.794 which was considered reliable. The study employed both descriptive and inferential statistics to present and analyze the data. The Statistical Package for Social Science (SPSS) a computer programme for windows aided the data analysis.The study established that talent attraction showed strong positive relationship against organizational performance in Public University Campuses in County Government of Nakuru with correlation of (r = 0.640, p < 0.05) . The study recommends that HR departments to be responsive to needs and constantly changing requirements of workforce in order to improve programmes and policies as need may be. It is also important that institutions adopt talent management to improve on its performance. The study also recommends that further research could be carried out in private universities to establish the differences